Impact of COVID-19 pandemic on the practice of pediatric dentistry in the United Arab Emirates: a cross-sectional survey - Hisham Yehia El Batawi; Zain Sawalha; Mai Almomani (SpringerOpen, 2022)
Abstract Background The aim of this study was to assess the impact of COVID-19 epidemic circumstances on the practice of pediatric dentistry in the United Arab Emirates. Methods An online questionnaire was distributed among members of Emirates Club of Pediatric Dentistry. The questionnaire was divided into three sections: (1) dentists' demographic characteristics, (2) general knowledge and attitude toward COVID-19, (3) practice of pediatric dentistry during COVID-19 pandemic. Results Female pediatric dentists were double the males and the age distribution tended towards the younger age group. Most of the participants had a satisfactory level of knowledge about COVID-19 and 100% of them obtained this knowledge from the health authorities. Around one third of the participants were not confident of their ability to work safely during the epidemic. There was a marked diversity between pediatric dentists regarding the priority services to be delivered to children during the COVID-19 peak. Conclusion A majority of pediatric dentists in the UAE are well informed regarding COVID-19 and its prevention. The economic impact of the epidemic has disrupted pediatric dentists' willingness to prioritize certain dental services over others. This is related to safety concerns, financial urge, and patient needs.